Narrowband ultraviolet B light treatment changes plasma concentrations of MMP-3, MMP-9 and TIMP-3 in psoriatic patients - Głażewska EK; Niczyporuk M; Ławicki S; Szmitkowski M; Donejko M; Zajkowska M; Będkowska GE; Przylipiak A (Dove Medical Press, 2017)
Edyta Katarzyna Głażewska,1 Marek Niczyporuk,1 Sławomir Ławicki,2 Maciej Szmitkowski,2 Magdalena Donejko,1 Monika Zajkowska,2 Grażyna Ewa Będkowska,3 Andrzej Przylipiak1 1Department of Esthetic Medicine, 2Department of Biochemical Diagnostics, 3Department of Haematological Diagnostics, Medical University, Bialystok, Poland Background: Matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) are thought to be associated with the pathogenesis and spread of psoriatic disease. This study was designed to investigate the plasma levels of MMP-3, MMP-9 and TIMP-3 in plaque psoriasis patients prior to and following a course of ultraviolet B narrowband treatment with respect to disease advancement.  Methods: Plasma samples of 49 patients suffering from plaque psoriasis and 40 healthy volunteers were evaluated. Concentrations of MMP-3, MMP-9 and TIMP-3 were determined using enzyme-linked immunosorbent assay, while Psoriasis Area and Severity Index was used to define disease advancement.  Results: Plasma levels of MMP-3, MMP-9 and TIMP-3 were significantly elevated in psoriasis patients compared to healthy individuals. A course of ultraviolet B narrowband treatment resulted in a significant decline in the studied metalloproteinases. Furthermore, the concentration of selected tissue inhibitors was negatively correlated with baseline Psoriasis Area and Severity Index score.  Conclusion: Our research highlights the meaningful role of MMP-3, MMP-9 and TIMP-3 in psoriasis pathogenesis and clearance of disease symptoms. Furthermore, plasma levels of the analyzed metalloproteinases seem to be a valuable psoriasis biomarker. Keywords: gelatinase B, stromelysin 1